Analisis Kinerja Ruas Jalan (Studi Kasus Jalan Tangkuban Perahu, Denpasar Barat) - I Wayan Gede Darma Yoga; Roger Bastiano Lica-Lica Dias Marcal; Dewa Ayu Putu Adhiya Garini Putri; Putu Ariawan (Reinforcement Review in Civil Engineering Studies and Management, 2022)
Denpasar city is one of the big cities that has a very high population, it can be seen from the population of Denpasar city of 962,900.000 million people, (BPS, 2020). Over time, the traffic density on the road has increased, in addition to the increasing number of residents and the increasing number of private vehicle ownership, it is also caused by the location adjacent to shopping centers and restaurants. This research was conducted using primary data. Primary data was obtained from survey results in the form of traffic survey data,Road Capacity, Degree of Saturation, and Level of Service using the 2014 PKJI method. Based on the results of the discussion, it can be concluded that the performance of the Tangkuban Perahu road is at Level of Service F, which means it is very bad, with the following indicators. The peak hour volume is 2394 cur/hour. Capacity 2381 cur/hour. The side resistance is 98,4, for the side resistance class it is classified as very low, which is 0.96. The degree of saturation (DJ) > 1.00 is 101 cur/hour. The average travel speed of vehicles at a distance of 100m is 21,69 km/hour.